Assessing the Prognostic Value of Extranodal Extension in Esophageal Cancer from the Pathological Staging Perspective. Issue 3 (7th February 2022) - Hayashi, Masato; Abe, Makoto; Fujita, Takeshi; Matsushita, Hisayuki
Abstract: Background: Extranodal extension (ENE) is a prognostic factor for several types of malignant tumors, including esophageal cancer. Although the prognostic value of ENE has been investigated in esophageal cancer, its clinical utility warrants further investigation. Materials and Methods: This retrospective single-center study evaluated 105 patients who underwent esophagectomy and had histologically node-positive metastasis between January 2007 and June 2017. The abilities of ENE to predict overall survival (OS) and disease-free survival (DFS) were evaluated using the Kaplan–Meier method and log-rank test, as well as Cox proportional hazard models. Subgroup analyses of ENE's prognostic value were performed according to each pathological tumor-node-metastasis category. Results: Significant differences according to ENE status were observed in the Kaplan–Meier analyses of OS ( p  = 0.001) and DFS ( p  = 0.001), as well as in the Cox proportional hazards models for OS ( p  = 0.009) and DFS ( p  = 0.012). Relative to patients without ENE, patients with ENE had significantly poorer OS if they also had pT3 status, pN1 status, or pathological stage III disease. However, no significant differences were observed in the subgroup analyses of pN3 status and pathological stage IV disease. Conclusions: Among patients with esophageal cancer, ENE status can predict a poor prognosis and may be useful for patient stratification. However, the prognostic value of ENE status may be limited to patients with specific pathological factors.